CHRISTIAN EDUCATIONAL MANAGEMENT PARADIGM FROM THE PERSPECTIVE OF THEOLOGY, PHILOSOPHY, AND CONTEMPORARY PRACTICE - Sarjani Jojor Martua Sianturi; Binur Panjaitan (RADJA PUBLIKA, 2025)
The paradigm of Christian educational management in the contemporary era is grounded in theological and philosophical foundations that affirm the necessity of orienting all educational management processes toward the holistic formation of the human person according to the values of the Kingdom of God. This study analyzes the paradigm of Christian educational management by integrating theological, philosophical, and contemporary management perspectives. A qualitative approach based on an in-depth literature review is employed, examining sources in the theology of education, Christian philosophy of education, and modern management theory to map the construction and transformation of the Christian educational management paradigm. The findings indicate that theological concepts such as imago Dei, the cultural mandate, and the spirituality of education serve as normative foundations within Christian educational management. The reformulation of the paradigm emerges through dialogue between theological values and modern management theories, producing a managerial approach that is more adaptive, integrative, and aligned with contemporary societal dynamics. This reformulation also carries significant epistemological implications for the aims of Christian education, particularly in strengthening holistic, transformational, and competence-oriented orientations. Furthermore, the paradigm's reformulation signals a notable epistemological shift toward a model of education that is holistic, transformative, and competence-driven while retaining its theological identity. The study underscores the importance of synthesizing faith, rationality, and managerial praxis in advancing Christian educational management in the modern era.